A study of three variable analogues of certain fractional integral operators - Khan, Mumtaz Ahmad; Sharma, Bhagwat Swaroop (Pro Mathematica, 2010)
The paper deals with a three variable analogues of certain fractional integral operators introduced by M. Saigo. Resides giving three variable analogues of earlier known fractional integral operators of one variable as a special cases of newly defined operators, the paper establishes certain results in the form of theorems including integration by parts.